Adverse events in British hospitals: preliminary retrospective record review. Issue 7285 (3rd March 2001) - Vincent, Charles; Neale, Graham; Woloshynowych, Maria
Abstract: Objectives: To examine the feasibility of detecting adverse events through record review in British hospitals and to make preliminary estimates of the incidence and costs of adverse events. Design: Retrospective review of 1014 medical and nursing records. Setting: Two acute hospitals in Greater London area. Main outcome measure: Number of adverse events. Results: 110 (10.8%) patients experienced an adverse event, with an overall rate of adverse events of 11.7% when multiple adverse events were included. About half of these events were judged preventable with ordinary standards of care. A third of adverse events led to moderate or greater disability or death. Conclusions: These results suggest that adverse events are a serious source of harm to patients and a large drain on NHS resources. Some are major events; others are frequent, minor events that go unnoticed in routine clinical care but together have massive economic consequences